Water vapour mixing ratio in the troposphere and its influence on the tropopause over India and neighbourhood . - RAMAMURTHY, K. (MAUSAM, 1976)
The distribution or water vapour mixing ratio in the troposphere over different stations in India and the three equatorial stations-Nairobi, Gan and Singapore- through the year has been studied with reference to the level of the tropopause over these stations to see if there is an, relationship between these two elements. Meridional distribution of water vapour mixing ratio along longitudes 730 E and 800 E during June and October has also be001 examined with reference to the tropopause level along these longitudes during these two months In addition the distribution of the mixing ratio and the level of tropopause during active and break monsoon spells during the years 1971 through 1973 has also been looked into. It is seen from these, that there is no unique or uniform relationship between the tropopause and water vapour mixing ratio over India and along the equator throughout the year.